Effect of pH and molar concentration on photocatalytic performance of BiVO4 synthesised by sol–gel method. (9th November 2016) - Wang, X.; Shen, Y.; Zuo, G.; Li, F.; Meng, Y.; Hou, L.
Abstract : In this study, a series of monoclinic BiVO4 photocatalysts were successfully synthesised by the sol–gel method by varying pH and molar concentration. The structural and morphological properties of the synthesised BiVO4 photocatalysts were characterised by X-ray diffraction and scanning electron microscopy, respectively. The photocatalytic activity of the catalysts was evaluated by the degradation of RhB under visible-light irradiation. The results indicate that at pH = 7, the catalysts showed the best photocatalytic activity, reaching up to 90.9%. Furthermore, at 0.2M concentration, the catalysts showed the best photocatalytic activity, reaching up to 89.4%. The catalysts synthesised at different pH and molar concentrations exhibited different photocatalytic activities under visible-light irradiation because different conditions led to different degrees of crystallinity and grain distributions of monoclinic BiVO4 .